Body fat percentage and CRP correlates with a composite score of vascular risk markers in healthy, young adults - The Lifestyle, Biomarkers, and Atherosclerosis (LBA) study - Pettersson-Pablo, Paul; Cao, Yang; Bäckström, Torbjörn; Nilsson, Torbjörn K.; Hurtig-Wennlöf, Anita (BMC cardiovascular disorders, 2020)
Background Identification of early signs of atherosclerosis in young adults have the potential to guide early interventions to prevent later cardiovascular disease. We therefore analyzed measures of vascular structure and function and biomarkers of cardiovascular risk in a sample of young healthy adults. Methods Pulse-wave velocity (PWV), carotid-intima media thickness (cIMT) and augmentation index (AIX) were measured in 834 healthy non-smokers (ages 18.0–25.9). Emphasis was put on discriminating between individuals having a vascular structure and function associated with a higher or lower risk, and cluster analysis algorithms were employed to assign the subjects into groups based on these vascular measurements. In addition, a vascular status score (VSS) was calculated by summarizing the results according to quintiles of the vascular measurements. The associations between VSS and cardiovascular biomarkers were examined by regression analyses. Results The cluster analyses did not yield sufficiently distinct clustering (groups of individuals that could be categorized unequivocally as having either a vascular structure and function associated with a higher or lower CVD risk). VSS proved a better classificatory variable. The associations between VSS and biomarkers of cardiovascular risk were analyzed by univariable and multivariable regressions. Only body fat percentage and C-reactive protein (CRP) were independently associated with VSS. Conclusions A VSS calculation, which integrates PWV, cIMT, and AIX measurements is better suited for cardiovascular risk evaluation in young adults than cluster analyses. The independent associations of VSS with body fat percentage and CRP highlight the decisive role of adiposity and systemic inflammation in early atherosclerotic progression and suggests a subordinate role of insulin and lipid metabolism in this age span.